2017
DOI: 10.1200/jco.2016.68.5651
|View full text |Cite
|
Sign up to set email alerts
|

Promoting End-of-Life Discussions in Advanced Cancer: Effects of Patient Coaching and Question Prompt Lists

Abstract: In einer Studie wurde untersucht, wie sich die Pege im Hospiz in der Wahrnehmung der Angehörigen auf das Benden und die Lebensqualität der Sterbenden auswirkt. I n der Studie wurden 2.307 Familien ver-storbener Patienten mit fortgeschritte-nem Lungen-oder Kolorektalkarzinom interviewt. Die Patienten waren im Rah-men der multiregionalen prospektiven Beobachtungsstudie Cancer Care Outcomes Research and Surveillance Study re-krutiert worden und schließlich verstor-ben. Verglichen wurden Familienberich-te über Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 34 publications
(3 reference statements)
0
71
1
1
Order By: Relevance
“…Coaches and trust persons are important for supporting patients in preparation for their consultation, accompanying patients to the consultation and discussing their emotions. Previous studies evaluated the effectiveness of a coach on patient participation in oncology consultations (e.g., Rodenbach et al, ; Street et al, ). These studies showed that a preparation session with a coach prior to a consultation increased the discussion of emotional topics such as prognosis (Rodenbach et al, ) and affected question‐asking behaviour, assertiveness and the expression of pain‐related concerns (Street et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coaches and trust persons are important for supporting patients in preparation for their consultation, accompanying patients to the consultation and discussing their emotions. Previous studies evaluated the effectiveness of a coach on patient participation in oncology consultations (e.g., Rodenbach et al, ; Street et al, ). These studies showed that a preparation session with a coach prior to a consultation increased the discussion of emotional topics such as prognosis (Rodenbach et al, ) and affected question‐asking behaviour, assertiveness and the expression of pain‐related concerns (Street et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Coaches and trust persons are important for supporting patients in preparation for their consultation, accompanying patients to the consultation and discussing their emotions. Previous studies evaluated the effectiveness of a coach on patient participation in oncology consultations (e.g., Rodenbach et al, 2017;Street et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient coaching and/or question prompt-lists have been shown to help engage patients in care decisions, improve understanding [5052] and potentially promote prognostic discussions. [53,54] If our intervention proves successful, combining IC video tools with question prompt lists or audio-recordings could be examined.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for combining the scores from each of the seven patient decision aids provided another outcome for data analysis, to attempt to identify any broad areas where patient decision aids within end-of-life care collectively may be lacking to support patient needs. The 'collective scores' were allocated to one of the three following categories, to represent the extent to which the patient decision aids collectively addressed each 'addressable' patient need: 'sufficient' (score: [22][23][24][25][26][27][28], 'variable' (score: [15][16][17][18][19][20][21], or 'insufficient' (score: 7-14).…”
Section: Search Two -Data Extraction Synthesis and Analysis (Objectimentioning
confidence: 99%